2018
DOI: 10.1007/s40195-018-0812-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mo Addition on Corrosion Behavior of High-Entropy Alloys CoCrFeNiMox in Aqueous Environments

Abstract: The corrosion behavior of CoCrFeNiMo x alloys was investigated in aqueous environments, NaCl and H 2 SO 4 solutions, respectively, to simulate typical neutral and acidic conditions. The cyclic polarization curves in NaCl and the potentiodynamic curves in H 2 SO 4 clearly reveal the beneficial effects of Mo and the detrimental effect of r-phase on the corrosion resistance. The X-ray photoelectron spectroscopy results of CoCrFeNiMo x alloys in H 2 SO 4 solution indicate that Cr and Mo predominate the corroded su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(52 citation statements)
references
References 75 publications
2
50
0
Order By: Relevance
“…The high Co concentration (15%) will also decrease the corrosion resistance of the alloys [27]. The corrosion behavior of CoCrFeNi-based HEAs, including Al, Cu, W, Mo and Ru [28][29][30][31][32][33], has been studied. Lee et al [28] investigated the corrosion performance of AlxCrFe1.5MnNi0.5(x=0,0.3,0.5) HEAs in 1M NaCl solution, and the results demonstrated that the addition of Al to the alloys reduces the resistance to pitting corrosion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high Co concentration (15%) will also decrease the corrosion resistance of the alloys [27]. The corrosion behavior of CoCrFeNi-based HEAs, including Al, Cu, W, Mo and Ru [28][29][30][31][32][33], has been studied. Lee et al [28] investigated the corrosion performance of AlxCrFe1.5MnNi0.5(x=0,0.3,0.5) HEAs in 1M NaCl solution, and the results demonstrated that the addition of Al to the alloys reduces the resistance to pitting corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…The corrosion behaviour of FeCoNiCrCux(x=0,0.5,1) HEA was studied in sulfuric acid, and it was suggested that the corrosion resistance of the alloys was deteriorated by the segregation of Cu resulting in galvanic corrosion [31]. The CoCrFeNiMox(x=0.1-0.5at%) HEAs demonstrated good corrosion resistance in Cl-containing solution due to the beneficial effect of Mo [32]. Scully et al [33] reported excellent passivity for 38Ni-21Cr-20Fe-13Ru-6Mo-2W HEA with the enrichment of Cr (48 at%) and small amount of Mo (8 at%) in the oxide film.…”
Section: Introductionmentioning
confidence: 99%
“…This fact indicates that the alloy showed no signs of severe corrosion, while some residues of the corrosion solution simply covered its surface. As such, the observation of the sample does not reveal any selective galvanic inter-dendritic corrosion as recorded in other systems of the literature [19][20][21][22][23][24].…”
Section: Corrosion Behavior Of Motanbvti Hea In 35 Wt% Nacl Solutionmentioning
confidence: 57%
“…Recently, a new alloy concept of high-entropy alloys (HEAs) or multicomponent alloys was proposed by Yeh et al [1] and Cantor et al [2]. HEAs generally contain principal elements with the concentration between 5 and 35 at% [3][4][5][6][7][8][9][10][11] and exhibit many excellent physical, chemical and mechanical properties, such as high strength and ductility [3,4,12,13], high fracture toughness [5,6], excellent corrosion resistance [7,8] and good irradiation resistance [9,10]. Thereinto, refractory high-entropy alloys (RHEAs) were designed using high-melting-point metals such as V, Nb, Ta, Mo, W, Ti, Zr and Hf, which possess high strength and excellent hightemperature softening resistance [11,14,15].…”
Section: Introductionmentioning
confidence: 99%